Enhancing bioethanol production from delactosed whey permeate by upstream desalination techniques. Issue 5 (11th May 2014) - Wagner, Christopher; Benecke, Christian; Buchholz, Heinrich; Beutel, Sascha
<x xml:space="preserve">Abstract</x> Industrial cheese whey processing comprises generally the isolation of proteins and lactose, but the economic use for the residual molasses, the so‐called delactosed whey permeate (DWP), is still to be improved. One possibility to maximize valorization and to minimize waste water treatment is the conversion of the remaining lactose in the DWP to ethanol by the yeast Kluyveromyces marxianus. This fermentation process depends strongly on the total ash content of the DWP, as high salt concentrations inhibit yeast metabolism. Here, three different approaches were tested to lower the DWP salt content: (i) simple dilution; (ii) nanofiltration; and (iii) electrodialysis. Lactose consumption, ethanol production and time‐dependent yields were compared between the three methods. A dilution of DWP to 60% v/v led to fermentation taking less than 80 h and yield above 7% AbV (alcohol by volume). After nanofiltration, 7.5% AbV was produced in about 80 h, and after electrodialysis, 11% AbV was produced in about 52 h. On the one hand the technical treatments (nanofiltration and electrodialysis) led to enhanced productivity in the fermentations, but, on the other hand, elaborate and extensive preprocessing is needed. Overall, ethanol production from DWP could be enhanced by prior partial desalination.